Narratives of pregnant women with AIDS: in search of a theoretical model for medical practice problems - Regina Rocco; Silvia Teresa Carvalho de Araújo; Isis Vanessa Nazareth; Luís Paulo José Marques; Valéria Cristina Soares Furtado Botelho; Teresa Tonini; Leila Rangel da Silva; Angela Maria Bittencourt Fernandes da Silva; Nébia Maria Almeida de Figueiredo (DST, 2022)
Introduction: In the care of pregnant women with acquired immunodeficiency syndrome (AIDS), it is often not clear who these patients are, how they behave in the face of diagnosis and pregnancy, how they live their disease, what it means for them to carry a child at risk, as well as the possibility of spreading the virus and not being able to breastfeed. Objective: To analyze the life memories of pregnant women with AIDS. Methods: This qualitative cartographic study sought to trace, touch, and understand what these women feel or remember about their lives through life narratives. Results: The sample consisted of ten women whose narratives generated three categories of living in the different life stages. The study produced a concentration of 515 units of analysis and analyzed 160 statements, with 11 themes related to memories about family dynamics and its problems. Conclusion: We expect to contribute to the renewal of the practice, discourse, and language, as an exclusive work and teaching network about the importance of listening to the human being when obtaining data outside our area of knowledge